2003
DOI: 10.1002/jmv.10578
|View full text |Cite
|
Sign up to set email alerts
|

The effect of highly active antiretroviral therapy for HIV on the anti‐HCV specific humoral immune response

Abstract: The effect of highly active antiretroviral therapy (HAART) on HCV replication is controversial, with some studies reporting no effect and others increases, reductions and even clearances of HCV RNA after treatment. In this study, the effect of HAART was investigated on the titre of anti-HCV specific antibodies and on the relationship between these antibodies and HCV RNA level in a cohort of 24 patients with inherited bleeding disorders. A significant inverse correlation between antibodies to both total HCV pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 51 publications
(56 reference statements)
0
2
1
Order By: Relevance
“…Although we have used a different analysis, our results contrasts strongly with published data on monoinfection, for which there is clear evidence for selection in the same region [14,37]. Furthermore, although previous data in coinfection have shown a significant humoral response against E1/E2 and an inverse correlation between antibody levels and HCV RNA load [38], our data also argue against a significant selective effect from the humoral immune response, although this was not formally investigated in our study.…”
Section: Discussioncontrasting
confidence: 81%
“…Although we have used a different analysis, our results contrasts strongly with published data on monoinfection, for which there is clear evidence for selection in the same region [14,37]. Furthermore, although previous data in coinfection have shown a significant humoral response against E1/E2 and an inverse correlation between antibody levels and HCV RNA load [38], our data also argue against a significant selective effect from the humoral immune response, although this was not formally investigated in our study.…”
Section: Discussioncontrasting
confidence: 81%
“…This decrease likely results from a lower HCV antibody level in HIV-infected patients in relation to a lack of recovery of specific humoral immune responses even after successful antiretroviral therapy. [28][29][30] Not surprisingly, the HCV POC sensitivity on FSB also seemed to be impacted by the HIV status with two out of the three observed false-negative results occurring in HIV/HCV co-infected patients. Other studies have found similar false-negative results for HCV/HIV co-infected patients using rapid tests.…”
Section: Discussionmentioning
confidence: 87%
“…In a three year study, HIV/HCV patients were unable to normalise circulating B-cell counts or serum total IgG levels [9]. Titres of HCV-reactive antibodies increased after 1 year of ART, with no changes in HCV viral loads [10].…”
Section: Introductionmentioning
confidence: 98%